2021
DOI: 10.1186/s40644-021-00388-5
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of magnetic resonance radiomic features to pixel size resampling and interpolation in patients with cervical cancer

Abstract: Background Radiomics is a promising field in oncology imaging. However, the implementation of radiomics clinically has been limited because its robustness remains unclear. Previous CT and PET studies suggested that radiomic features were sensitive to variations in pixel size and slice thickness of the images. The purpose of this study was to assess robustness of magnetic resonance (MR) radiomic features to pixel size resampling and interpolation in patients with cervical cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 32 publications
(47 reference statements)
1
40
0
Order By: Relevance
“…As such, we performed standardized anisotropic resampling for all MRI sequences to ensure reproducibility as also performed in prior MRI radiomic studies [ 19 , 20 ]. Moreover, radiomic features have also been shown to be robust to different levels of pixel spacing and interpolation [ 21 ]. In addition, feature standardization (also performed in our study) has been shown to improve robustness of radiomic features beyond pixel spacing and interpolation [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, we performed standardized anisotropic resampling for all MRI sequences to ensure reproducibility as also performed in prior MRI radiomic studies [ 19 , 20 ]. Moreover, radiomic features have also been shown to be robust to different levels of pixel spacing and interpolation [ 21 ]. In addition, feature standardization (also performed in our study) has been shown to improve robustness of radiomic features beyond pixel spacing and interpolation [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Feature selection was performed using the recipes package in R version 4.0.2 [ 34 , 35 ]. All features were standardized using the z-score transformation prior to feature selection [ 21 ]. In patients with any missing mask (absence of necrotic/edema masks), radiomic features were not calculated, and in those, the missing values were imputed using mean imputation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grayscale normalization improves the robustness of radiomics features [32,33]. As with T2, we applied z-score normalization to the post contrast enhanced MRI during the preprocessing stage.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Indeed, each step of the radiomic work ow (i.e., image acquisition and reconstruction, image segmentation, image preprocessing, image ltering, and feature extraction) could in uence features estimation, thus potentially affecting their discriminative or predictive power 37,38 . Several previous studies have assessed the sensitivity of radiomic features estimation to various elements in computed tomography (CT) [39][40][41] and nuclear medicine (NM) 42,43 imaging, as well as in magnetic resonance imaging (MRI), for various applications [44][45][46][47][48][49][50][51][52][53][54][55] .…”
Section: Introductionmentioning
confidence: 99%